Adopting and contextualising international computing curricula: a South African case - Mashingaidze, Kenneth Tatenda (My University, 2017)
Purpose – The aim of this research is to examine one case of the adoption and contextualisation of an international computing curriculum at a South African university in order to improve the understanding of this process for literature as well as practice. An international computing curriculum is a curriculum developed by international professional and scientific bodies such as the Association for Information Systems (AIS), Institute for Electrical and Electronics Engineers (IEEE) or the Association for Computing Machinery (ACM). Design/methodology/approach – The research adopts an interpretivist approach and follows an exploratory research design using qualitative methods to gather data and directed content analysis for data analysis. The research site is a traditional South African university which has used the IS2010 curriculum as a guideline for their undergraduate Information Systems degrees. The site was chosen using convenience sampling. Data was obtained through interviews with staff at the Information Systems department as well as university documentation. Findings - The research indicates that university objectives, university context and industry skills needs have shaped the way the university has adopted and contextualised the IS2010 curriculum. The research also indicates that there are two types of challenges that were encountered: challenges caused by IS2010 and existing challenges that affected IS2010. The major challenges caused by IS2010 were the absence of important elements related to teaching and learning, particularly pedagogy. The challenges that affected the adoption of IS2010 but were not caused by IS2010 were challenges that the university was already facing. These include the language of instruction, institutional culture, staff shortages and students’ cultural and educational background. Originality and Practical contribution – Most of the research on this area focuses on African countries other than South Africa. Researchers have argued that it is important to conduct this kind of research on an individual country level because of the unique nature of the challenges facing each country. This research is an attempt to conduct such research specifically for South Africa. The research findings have shed light on how a South African university may adopt and contextualise an international computing curriculum and the challenges the university might face in doing so. This will in turn help computing educators in addressing such challenges and provide some guidance on how to go about doing so. The research also puts forward a conceptual framework that can be used to research computing curriculum contextualisation in South Africa.
Submitted in partial fulfilment of an M.Com. degree in Information Systems, Faculty of Commerce, Law and Management, University of the Witwatersrand, March 2017
Keywords: Computer science--Study and teaching (Higher)--South Africa; Information technology--Study and teaching (Higher)--South Africa